PENGARUH TINDAKAN MOBILISASI DINI TERHADAP DENYUT JANTUNG DAN FREKUENSI PERNAPASAN PADA PASIEN KRITIS DI ICU RSUD SLEMAN YOGYAKARTA - Nofiyanto, Muhamat; Saktika Adhinugraha, Tetra (MEDIA ILMU KESEHATAN, 2016)
Background: Patients with critical conditions in the ICU depend on a variety of tools to support their lifes. Patients’ conditions and and their unstable hemodynamic are challenges for nurses to perform mobilization. Less mobilization in critical patients can cause a variety of physical problems, one of them is cardiorespiratory function disorder. Objective: to investigate differences in heart rate (HR) and respiratory rate (RR) before, during, and immediately after early mobilization. Methods: This study employed quasi experiment with one group pre and post test design. Twenty four respondents were selected based on the criteria HR <110 / min at rest, Mean Arterial Blood Pressure between 60 to 110 mmHg, and the fraction of inspired oxygen <0.6. Early mobilization was performed to the respondents, and followed by assessments on the changes of respiratory rate and heart rate before, during, and immediately after the mobilization. Analysis of differences in this study used ANNOVA. Results: Before the early mobilization, mean RR was 22.54 and mean HR was 78.58. Immediately after the mobilization, mean RR was 23.21 and mean HR was 80.75. There was no differences in the value of RR and HR, before and immediately after the early mobilization with the p-value of 0.540 and 0.314, respectively. Conclusions: Early mobilization of critical patients is relatively safe. Nurses are expected to perform early mobilization for critical patients. However, it should be with regard to security standards and rigorous assessment of the patient's conditions. Keywords: Early mobilization, critical patients, ICU